Thermoplastic resin composition

By using polyolefin-polystyrene-based multi-block copolymer in the thermoplastic resin composition and optimizing the tan δ peak height and half width in dynamic thermomechanical analysis, the problem of taking into account both the fluidity and resilience of the material in the prior art is solved, and a thermoplastic resin composition with high flowability and high resilience is achieved.

CN116209719BActive Publication Date: 2025-03-28LG CHEM LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180059928.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-08-05
Filing Date
2021-08-06
Publication Date
2025-03-28
Estimated Expiration
2041-08-06

AI Technical Summary

Technical Problem

The prior art is difficult to provide materials with softness and high resilience while maintaining high fluidity, especially in the mixing of polypropylene and ethylene-α-olefin copolymers, where impact strength and resilience are limited.

Method used

A thermoplastic resin composition comprising polypropylene and polyolefin-polystyrene-based multiblock copolymers that meet specific tan delta peak height and half-width conditions in dynamic thermomechanical analysis to ensure excellent viscoelastic properties of the material in temperature range of -80°C to 40°C.

Benefits of technology

It achieves a balance between high fluidity, softness and high resilience, improves the impact strength and processability of the material, and is suitable for a variety of application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116209719B_ABST
    Figure CN116209719B_ABST
Patent Text Reader

Abstract

The present invention relates to a thermoplastic resin composition comprising a polyolefin-polystyrene-based multi-block copolymer having a structure in which a polystyrene chain is connected to both ends of a polypropylene and a polyolefin chain, and the thermoplastic resin composition of the present invention exhibits high fluidity as well as soft feeling and high resilience.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of Korean Patent Application No. 10-2020-0099168, filed on August 7, 2020, and Korean Patent Application No. 10-2021-0103396, filed on August 5, 2021, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety.

[0002] The present invention relates to a thermoplastic resin composition comprising a polyolefin-polystyrene-based multi-block copolymer having a structure in which a polystyrene chain is connected to both ends of a polypropylene chain and a polyolefin chain. Background Art

[0003] Polypropylene, which is widely used as a handle for household goods or a material for automotive interior and exterior parts, has the advantages of excellent rigidity and molding processability, but has the disadvantage of weak impact strength. Therefore, in order to overcome the above problems, a polypropylene resin composition comprising polypropylene (PP) as a main component and an impact-resistant reinforcing material and an inorganic filler has been used. Due to the introduction of ethylene-α-olefin copolymers synthesized by metallocene catalysts, ethylene-α-olefin copolymers have been used as impact-resistant reinforcing materials for polypropylene. The advantage of the mixed composition of polypropylene and ethylene-α-olefin copolymers as described above is that the weak impact strength of polypropylene is compensated, and the low rigidity of ethylene-α-olefin copolymers is compensated.

[0004] However, when polypropylene is mixed with ethylene-α-olefin copolymer, the softness and resilience of the ethylene-α-olefin copolymer are significantly reduced even if a small amount of polypropylene is added, and even if the impact strength is compensated by adding the ethylene-α-olefin copolymer to the polypropylene, there is still a limitation in ensuring impact resistance according to various usage environments.

[0005] Therefore, for materials requiring soft feel and high resilience, styrene-ethylene-butylene-styrene (SEBS), ie, styrene-based thermoplastic elastomers, have also been used with polypropylene. However, SEBS is expensive and has the problem of significantly reducing the fluidity of polypropylene, resulting in flow marks or underfilling.

[0006] Therefore, there is still a need to develop a thermoplastic resin composition having a soft feel and high resilience while maintaining high fluidity.

[0007] [Prior art literature]

[0008] [Patent Document]

[0009] (Patent Document 1) Korean Patent Application Publication No. 10-1657925. Summary of the invention

[0010] Technical issues

[0011] One aspect of the present invention provides a thermoplastic resin composition having excellent restoring force while having high fluidity.

[0012] Technical Solution

[0013] According to one aspect of the present invention, there is provided a thermoplastic resin composition comprising: (1) polypropylene; and (2) a polyolefin-polystyrene-based multi-block copolymer, which satisfies the following conditions (a) and (b) in a temperature range of -80°C to 40°C in a graph showing the amount of change in loss tangent (tan δ) (y-axis) with temperature (x-axis) obtained by dynamic thermomechanical analysis (DMA).

[0014] (a) The height of the tan δ peak is 0.45 to 0.60; (b) The half width of the tan δ peak is 22.5°C to 30.0°C.

[0015] Beneficial effects

[0016] The thermoplastic resin composition of the present invention exhibits high fluidity as well as soft feel and high resilience. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The ligand compound used in preparing the polyolefin-polystyrene multi-block copolymer contained in the thermoplastic resin composition according to one embodiment of the present invention is shown. 1 H NMR and 13 C NMR spectrum;

[0018] Figure 2 The transition metal compound used in preparing the polyolefin-polystyrene multi-block copolymer contained in the thermoplastic resin composition of one embodiment of the present invention is shown. 1 H NMR and 13 C NMR spectrum. DETAILED DESCRIPTION

[0019] Hereinafter, the present invention will be described in more detail to facilitate understanding of the present invention.

[0020] It will be understood that the words or terms used in the specification and claims of the present invention should not be interpreted as limited to having the meaning defined in the commonly used dictionary. It will also be understood that the words or terms should be interpreted as having a meaning consistent with their meaning in the context of the relevant art and the context of the technical idea of ​​the present invention based on the principle that the inventor can appropriately define the meaning of the words or terms to best explain the present invention.

[0021] As used herein, the term "composition" includes not only reaction products and decomposition products formed from the materials of the corresponding composition, but also includes mixtures comprising the materials of the corresponding composition.

[0022] The term "polymer" as used herein refers to a polymer compound prepared by polymerizing monomers, whether of the same or different types. Thus, the generic term "polymer" encompasses the term "homopolymer" (usually employed to refer to polymers prepared from only one type of monomer) and the term "interpolymer" as defined below.

[0023] The term "interpolymer" as used herein refers to a polymer prepared by the polymerization of at least two different monomers. Thus, the general term "interpolymer" encompasses the term "copolymer" (usually used to refer to a polymer prepared from two different monomers) and the term "polymer" prepared from more than two different monomers.

[0024] Hereinafter, the present invention will be described in detail.

[0025] The thermoplastic resin composition of the present invention comprises: (1) polypropylene; and (2) a polyolefin-polystyrene-based multi-block copolymer, which satisfies the following conditions (a) and (b) in a temperature range of -80°C to 40°C in a graph showing the amount of change in loss tangent (tan δ) (y-axis) with temperature (x-axis) obtained by dynamic thermomechanical analysis (DMA).

[0026] (a) The height of the tan δ peak is 0.45 to 0.60;

[0027] (b) The half width of the tan δ peak is 22.5°C to 30.0°C.

[0028] Hereinafter, the various constituent components will be described in more detail.

[0029] (1) Polypropylene

[0030] In the thermoplastic resin composition according to one embodiment of the present invention, the polypropylene may specifically be a polypropylene homopolymer, or a copolymer of propylene and an α-olefin monomer, wherein the copolymer may be an alternating, random or block copolymer.

[0031] The α-olefin monomer may specifically be an aliphatic olefin having 2 to 12 carbon atoms, or 2 to 8 carbon atoms. More specifically, examples thereof may be ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-eicosene, 4,4-dimethyl-1-pentene, 4,4-diethyl-1-hexene or 3,4-dimethyl-1-hexene, and any one thereof or a mixture of two or more thereof may be used.

[0032] More specifically, the polypropylene may be any one or a mixture of two or more selected from the group consisting of polypropylene copolymers, propylene-α-olefin copolymers and propylene-ethylene-α-olefin copolymers, wherein the copolymer may be a random or block copolymer.

[0033] In addition, the melt index (MI) of the polypropylene measured at 230° C. and a load of 2.16 kg may be 0.5 g / 10 min to 100 g / 10 min. Specifically, the melt index (MI) may be 1 g / 10 min to 90 g / 10 min. When the melt index of the polypropylene exceeds the above range, there is a possibility that problems may occur during the injection molding process of the thermoplastic resin composition.

[0034] Specifically, in the thermoplastic resin composition of one embodiment of the present invention, the polypropylene can be an impact copolymer having a melt index (MI) of 0.5 g / 10 min to 100 g / 10 min, particularly 1 g / 10 min to 90 g / 10 min, measured at 230 ° C and 2.16 kg load, or more specifically, a polypropylene-ethylene impact copolymer. Based on the total weight of the polypropylene composite material, the content of the impact copolymer can be 20 wt % to 90 wt %, particularly 30 wt % to 70 wt %, and more particularly 40 wt % to 60 wt %. When an impact copolymer having the above-mentioned physical properties within the above-mentioned content range is included as the polypropylene, strength properties, particularly room temperature strength properties, can be improved.

[0035] The impact copolymer can be prepared by a general polymer preparation reaction to meet the above physical property requirements, or it can be commercially obtained and used. A specific example thereof can include LG Chem's product SEETEC TM M1600, etc.

[0036] In addition, in the thermoplastic resin composition of one embodiment of the present invention, the polypropylene may be specifically one or more random propylene copolymers having a DSC melting point of 120°C to 160°C and a melt flow rate (MFR) of 5g / 10min to 120g / 10min measured under the conditions of 230°C and 2.16kg load according to ASTM-D 1238. Based on the total weight of the polypropylene-based composite material, the content of the random propylene copolymer may be 20 wt% to 90 wt%, particularly 30 wt% to 70 wt%, and more particularly 40 wt% to 60 wt%. When the polypropylene having the above-mentioned physical properties within the above-mentioned content range is included, the mechanical strength of the thermoplastic resin composition, such as hardness, can be improved. The random propylene copolymer can be prepared using a general polymer preparation reaction to meet the above-mentioned physical property requirements, or it can be commercially available and used. Specific examples thereof may include Braskem America Inc.'s Braskem TM PP R7021-50RNA, Formolene from Formosa Plastics Corporation of the United States TM 7320A, etc.

[0037] (2) Polyolefin-polystyrene multi-block copolymers

[0038] In the thermoplastic resin composition of one embodiment of the present invention, the polyolefin-polystyrene-based multi-block copolymer is characterized in that the following conditions (a) and (b) are satisfied in the temperature range of -80°C to 40°C in a graph showing the amount of change in loss tangent (tan δ) (y-axis) with temperature (x-axis) obtained by dynamic thermomechanical analysis (DMA).

[0039] (a) the height of the tan δ peak is from 0.45 to 0.60; and

[0040] (b) The half width of the tan δ peak is 22.5°C to 30.0°C.

[0041] The loss tangent (tan δ) value refers to the ratio (E" / E') of the loss modulus (E") representing the viscosity of the material to the storage modulus (E') representing the elasticity of the material, and is used as an index for evaluating the viscoelasticity of the copolymer.

[0042] Regarding the above condition (a), for the polyolefin-polystyrene-based multi-block copolymer contained in the thermoplastic resin composition of one embodiment of the present invention, when the tan δ value is measured with temperature and represented as a graph with temperature as the x-axis and tan δ as the y-axis, the tan δ peak height in the temperature range of -80°C to 40°C is 0.45 to 0.60. Specifically, the tan δ peak height may be greater than or equal to 0.45, greater than or equal to 0.47, greater than or equal to 0.48, or greater than or equal to 0.50, or may be less than or equal to 0.60, less than or equal to 0.58, less than or equal to 0.57, or less than or equal to 0.55.

[0043] The tan δ peak height indicates the y value when the tan δ value is maximum in the range of -80°C to 40°C on the x-axis. In this case, the tan δ peak may appear as one peak in the range of -50°C to -30°C.

[0044] When the tan δ peak height is too small, the loss modulus value is small relative to the storage modulus, so that there may be problems of reduced degree of dispersion energy and lower impact strength, while when the tan δ peak height is too large, there may be a problem of reduced bending rigidity of the copolymer.

[0045] Regarding the above condition (b), the polyolefin-polystyrene-based multi-block copolymer has the above tan δ peak height and a tan δ peak half width of 22.5° C. to 30.0° C. Specifically, the tan δ peak half width may be greater than or equal to 22.5° C., greater than or equal to 23.0° C., greater than or equal to 24.0° C., greater than or equal to 25.0° C., greater than or equal to 25.5° C., or greater than or equal to 26.0° C., or may be less than or equal to 30.0° C., less than or equal to 29.0° C., or less than or equal to 28.5° C.

[0046] When the temperatures at which the half-values ​​of the tan δ peak heights each having the tan δ value defined in condition (a) are T1 (low temperature) and T2 (high temperature), respectively, the tan δ peak half-width refers to T2-T1, which is the temperature range between T1 and T2, and can be used as an indicator to explain how the distribution of tan δ values ​​in the copolymer changes with temperature. The narrower the tan δ peak half-width, the faster the copolymer can transition from the glass phase to the rubber phase. Therefore, the narrower the tan δ peak half-width, the higher the impact strength, and thus the copolymer can be effectively used as an impact-resistant reinforcing material.

[0047] When the tan δ peak half width is too large, there may be a problem that the impact strength of the copolymer is reduced, and therefore, when used as an impact-resistant reinforcing material, a sufficient effect may not be exhibited.

[0048] As described above, the polyolefin-polystyrene multiblock copolymer contained in the thermoplastic resin composition according to one embodiment of the present invention satisfies both conditions (a) and (b) and exhibits excellent impact strength, and thus can be widely used as an impact-reinforcing material in various fields.

[0049] The polyolefin-polystyrene multi-block copolymer may also satisfy the following conditions (c) and (d).

[0050] (c) a tan delta value of 0.10 to 0.30 at -10°C to -30°C;

[0051] (d) The tan δ value at 15°C to 30°C is 0.05 to 0.50.

[0052] Conditions (c) and (d) satisfy the change and distribution of the tanδ value with temperature as in the above conditions (a) and (b), respectively, and quantitatively express the tanδ value at low temperature and high temperature, respectively. The larger the loss modulus value and the smaller the storage modulus value, the larger the tanδ value, which means that when an impact is applied to the copolymer, the energy transferred from the impact can be effectively dispersed, and therefore, the copolymer can be used as an impact-resistant reinforcing material due to its excellent degree of withstanding impact.

[0053] Regarding the above condition (c), the tanδ value at -10°C to -30°C may be 0.10 to 0.30, particularly greater than or equal to 0.10, greater than or equal to 0.15, or greater than or equal to 0.17, or may be less than or equal to 0.30, less than or equal to 0.25, or less than or equal to 0.21. In addition, when the above range of tanδ values ​​is met, the storage modulus value E' may be 1 to 200 MPa, and the loss modulus value E" may be 1 to 100 MPa.

[0054] Regarding the above condition (d), the tanδ value at 15°C to 30°C may be 0.05 to 0.50, particularly greater than or equal to 0.05 or greater than or equal to 0.06, or may be less than or equal to 0.50, less than or equal to 0.40, less than or equal to 0.30, less than or equal to 0.20, or less than or equal to 0.10. In addition, when the above range of tanδ values ​​is met, the storage modulus value E' may be 0.1 to 50 MPa, and the loss modulus value E" may be 0.01 to 5 MPa.

[0055] As described above, the copolymer contained in the thermoplastic resin composition according to an embodiment of the present invention satisfies the tan δ values ​​of conditions (c) and (d), and thus exhibits excellent impact strength at low temperatures of -10°C to -30°C and high temperatures of 15°C to 30°C.

[0056] The weight average molecular weight of the polyolefin-polystyrene multi-block copolymer may be 40,000 to 300,000 g / mol, specifically greater than or equal to 50,000 g / mol, greater than or equal to 60,000 g / mol, or greater than or equal to 70,000 g / mol, or less than or equal to 250,000 g / mol, less than or equal to 220,000 g / mol, or less than or equal to 210,000 g / mol.

[0057] In addition, the molecular weight distribution of the polyolefin-polystyrene multi-block copolymer may be 1.0 to 3.0, specifically greater than or equal to 1.5 or greater than or equal to 1.6, or may be less than or equal to 3.0, less than or equal to 2.5, less than or equal to 2.0, or less than or equal to 1.9.

[0058] The weight average molecular weight and the number average molecular weight are polystyrene-equivalent molecular weights analyzed by gel permeation chromatography (GPC), and the molecular weight distribution is calculated from the ratio of (weight average molecular weight) / (number average molecular weight).

[0059] The polyolefin-polystyrene multi-block copolymer can be one or more selected from the group consisting of polystyrene-poly(ethylene-co-propylene)-polystyrene block copolymer, polystyrene-poly(ethylene-co-1-butene)-polystyrene block copolymer, polystyrene-poly(ethylene-co-1-pentene)-polystyrene block copolymer, polystyrene-poly(ethylene-co-1-hexene)-polystyrene block copolymer, polystyrene-poly(ethylene-co-1-heptene)-polystyrene block copolymer and polystyrene-poly(ethylene-co-1-octene)-polystyrene block copolymer.

[0060] In addition, the polyolefin block of the polyolefin-polystyrene-based multi-block copolymer contained in the thermoplastic resin composition of the present invention may include one or more repeating units represented by the following Chemical Formula a.

[0061] [Chemical formula a]

[0062]

[0063] In the above chemical formula a,

[0064] R1 may be hydrogen, an alkyl group having 1 to 20 carbon atoms, an alkyl group having 1 to 20 carbon atoms substituted with a silyl group, an arylalkyl group having 7 to 20 carbon atoms, or an arylalkyl group having 7 to 20 carbon atoms substituted with a silyl group, and

[0065] n may be an integer from 1 to 10,000.

[0066] Alternatively, according to one embodiment of the present invention, R1 may be hydrogen or an alkyl group having 3 to 20 carbon atoms.

[0067] Alternatively, according to one embodiment of the present invention, R1 may be hydrogen or an alkyl group having 3 to 12 carbon atoms. In particular, R1 may be hydrogen or an alkyl group having 4 to 12 carbon atoms.

[0068] Alternatively, n may be an integer from 10 to 10,000. In particular, n may be an integer from 500 to 7,000.

[0069] Meanwhile, in the chemical formulas shown in the specification of the present invention, "*" is the terminal part of the repeating unit and represents the connection site.

[0070] When the polyolefin block includes two or more repeating units represented by the above chemical formula a, the polyolefin block may include the repeating unit represented by the following chemical formula b.

[0071] [Chemical formula b]

[0072]

[0073] In the above chemical formula b,

[0074] R1' and R1" are each independently hydrogen, an alkyl group having 1 to 20 carbon atoms, an alkyl group having 1 to 20 carbon atoms substituted with a silyl group, an arylalkyl group having 7 to 20 carbon atoms, or an arylalkyl group having 7 to 20 carbon atoms substituted with a silyl group, where R1' and R1" are different from each other.

[0075] 0 < p < 1, and

[0076] n' may be an integer from 1 to 10,000.

[0077] Alternatively, according to one embodiment of the present invention, R1' and R1" may each independently be hydrogen or an alkyl group having 3 to 20 carbon atoms, particularly may each independently be hydrogen or an alkyl group having 3 to 12 carbon atoms, and more particularly may each independently be hydrogen or an alkyl group having 4 to 12 carbon atoms.

[0078] Alternatively, n' may specifically be an integer from 10 to 10,000, and more specifically may be an integer from 500 to 7,000.

[0079] According to one embodiment of the present invention, in the above chemical formula b, either R1' or R1" may be hydrogen, and the other may be a substituent other than hydrogen among the above substituents.

[0080] That is, when the polyolefin block includes two or more repeating units represented by the above chemical formula a, a structure in which R1 is hydrogen and a structure in which R1 is an alkyl group having 1 to 20 carbon atoms other than hydrogen, an alkyl group having 1 to 20 carbon atoms substituted with a silyl group, an arylalkyl group having 7 to 20 carbon atoms, or a structure in which R1 is an alkyl group having 7 to 20 carbon atoms substituted with a silyl group may be randomly connected. In particular, a structure in which R1 is hydrogen and a structure in which R1 is an alkyl group having 3 to 20 carbon atoms other than hydrogen may be randomly connected.

[0081] Alternatively, more specifically, the polyolefin block may have a structure in which R1 is hydrogen and a structure in which R1 is an alkyl group having 3 to 12 carbon atoms randomly connected to each other. Still more specifically, the polyolefin block may have a structure in which R1 is hydrogen and a structure in which R1 is an alkyl group having 4 to 12 carbon atoms randomly connected to each other.

[0082] When the polyolefin block includes two or more repeating units represented by the above Chemical Formula a, the polyolefin block may include a structure in which R1 is hydrogen and a structure in which R1 has a substituent other than hydrogen in the above Chemical Formula a at a weight ratio of 30:90 to 70:10, specifically at a weight ratio of 40:60 to 60:40, more specifically at a weight ratio of 45:75 to 55:25.

[0083] When the polyolefin block includes a structure in which R1 in the above chemical formula a is hydrogen and a structure in which R1 has a substituent other than hydrogen within the above range, the prepared block copolymer includes an appropriate degree of branching in the structure, and therefore has a very high 300% modulus value and a very high elongation at break value, thereby showing excellent elastic properties, and also shows a high molecular weight and a wide molecular weight distribution, and therefore, can have excellent processability.

[0084] Furthermore, the first polystyrene block of the polyolefin-polystyrene-based multi-block copolymer included in the thermoplastic resin composition of the present invention may include one or more repeating units represented by the following Chemical Formula c.

[0085] [Chemical formula c]

[0086]

[0087] In the above chemical formula c,

[0088] R2 is an aryl group having 6 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms substituted with halogen, an alkyl group having 1 to 12 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, or an aryl group having 6 to 12 carbon atoms, and

[0089] l is an integer from 10 to 1,000.

[0090] R2 may be phenyl, or phenyl which is unsubstituted or substituted with halogen, alkyl of 1 to 8 carbon atoms, cycloalkyl of 3 to 12 carbon atoms, alkoxy of 1 to 8 carbon atoms, or aryl of 6 to 12 carbon atoms. Alternatively, R2 may be phenyl.

[0091] l is an integer of 10 to 1,000, and specifically may be an integer of 50 to 700. When l is within the above range, the viscosity of the polyolefin-polystyrene block copolymer produced by the production method of the present invention may be at an appropriate level.

[0092] In particular, in the polyolefin-polystyrene-based multi-block copolymer contained in the thermoplastic resin composition of the present invention, the polyolefin block including the repeating unit represented by the above Chemical Formula a and the first polystyrene block including the repeating unit represented by the above Chemical Formula c can be combined with each other to form a composite block represented by the following Chemical Formula d.

[0093] [Chemical formula d]

[0094]

[0095] In the above chemical formula d,

[0096] R1 may be hydrogen, an alkyl group having 1 to 20 carbon atoms, an alkyl group having 1 to 20 carbon atoms substituted with a silyl group, an arylalkyl group having 7 to 20 carbon atoms, or an arylalkyl group having 7 to 20 carbon atoms substituted with a silyl group, and

[0097] R2 is an aryl group having 6 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms substituted with halogen, an alkyl group having 1 to 12 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, or an aryl group having 6 to 12 carbon atoms,

[0098] l is an integer from 10 to 1,000, and

[0099] n is an integer from 1 to 10,000.

[0100] Alternatively, in the above Chemical Formula d, R1, R2, l and n are the same as defined in Chemical Formula a and Chemical Formula c, respectively.

[0101] Alternatively, when the polyolefin block includes the repeating unit represented by the above Chemical Formula a, the composite block formed by combining the first polystyrene block including the repeating unit represented by the above Chemical Formula c may be represented by the following Chemical Formula e.

[0102] [Chemical formula e]

[0103]

[0104] In the above chemical formula e, R1′, R1″, R2, p, l and n′ are the same as defined in chemical formula a or c, respectively.

[0105] In addition, in one example of the present invention, when preparing a polyolefin-polystyrene multi-block copolymer, a styrene monomer may form a polyolefin block, and a styrene monomer may simultaneously combine with an organic zinc compound and polymerize to form another styrene polymer block. In the present disclosure, the other styrene polymer block is represented as a second polystyrene block. The second polystyrene block may include a repeating unit represented by the following chemical formula f.

[0106] [Chemical formula f]

[0107]

[0108] In the above chemical formula f,

[0109] R3 is an aryl group having 6 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms substituted with halogen, an alkyl group having 1 to 12 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, or an aryl group having 6 to 12 carbon atoms, and

[0110] m is an integer from 10 to 1,000.

[0111] Alternatively, according to one embodiment of the present invention, R3 may be a phenyl group, or a phenyl group which is unsubstituted or substituted with a halogen, an alkyl group of 1 to 8 carbon atoms, a cycloalkyl group of 3 to 12 carbon atoms, an alkoxy group of 1 to 8 carbon atoms, or an aryl group of 6 to 12 carbon atoms. Alternatively, R3 may be a phenyl group.

[0112] m is an integer of 10 to 1,000, and specifically may be an integer of 50 to 700.

[0113] That is, the polyolefin-polystyrene-based multi-block copolymer included in the thermoplastic resin composition of the present invention may include a first polystyrene block including a repeating unit represented by the above Chemical Formula c, and a second polystyrene block represented by the above Chemical Formula f.

[0114] Therefore, the block copolymer composition may include a triblock copolymer comprising a polyolefin block comprising one or more repeating units represented by the following Chemical Formula a, a first polystyrene block comprising a repeating unit represented by the following Chemical Formula c, and a second polystyrene block comprising a repeating unit represented by the following Chemical Formula f.

[0115] [Chemical formula a]

[0116]

[0117] [Chemical formula c]

[0118]

[0119] [Chemical formula f]

[0120]

[0121] In the above formula,

[0122] R1 is hydrogen, an alkyl group having 1 to 20 carbon atoms, an alkyl group having 1 to 20 carbon atoms substituted with a silyl group, an arylalkyl group having 7 to 20 carbon atoms, or an arylalkyl group having 7 to 20 carbon atoms substituted with a silyl group,

[0123] R2 and R3 are aryl groups having 6 to 20 carbon atoms, or aryl groups having 6 to 20 carbon atoms substituted with halogen, alkyl groups having 1 to 12 carbon atoms, cycloalkyl groups having 3 to 12 carbon atoms, alkoxy groups having 1 to 8 carbon atoms, or aryl groups having 6 to 12 carbon atoms,

[0124] n is an integer from 10 to 10,000, and

[0125] l and m are each independently an integer of 10 to 1,000.

[0126] Alternatively, in the above chemical formula, R1, R2, R3, n, l and m are the same as defined in chemical formulas a, c and f, respectively.

[0127] Preparation method of polyolefin-polystyrene multi-block copolymer

[0128] A method for preparing a polyolefin-polystyrene multi-block copolymer, characterized by comprising: (S1) in the presence of a catalyst composition comprising a transition metal compound represented by the following chemical formula 1, by polymerizing olefin monomers to form polyolefin blocks by using an organic zinc compound as a chain transfer agent, and (S2) in the presence of an alkyl lithium compound containing a silicon atom and a triamine compound, by anionic polymerization of the polyolefin blocks and styrene monomers to form polystyrene blocks.

[0129] The method for preparing a polyolefin-polystyrene multi-block copolymer can form a polyolefin chain by using a transition metal compound represented by Chemical Formula 1 which is effective for polymerization of an olefin monomer as a catalyst, and then continuously performing styrene anion polymerization to form a polyolefin-polystyrene block described later, thereby forming a polyolefin-polystyrene multi-block copolymer showing a specific height of a tan δ peak and a tan δ peak half width.

[0130] Step (S1)

[0131] The step (S1) is a step of forming a polyolefin block by polymerizing an olefin-based monomer using an organic zinc compound as a chain transfer agent in the presence of a catalyst composition including a transition metal compound represented by the following Chemical Formula 1.

[0132] [Chemical formula 1]

[0133]

[0134] In the above chemical formula 1,

[0135] R1 to R 11 each independently represents hydrogen, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an alkynyl group having 2 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an arylalkoxy group having 7 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, an alkylaryl group having 7 to 20 carbon atoms, an alkylsilyl group having 1 to 20 carbon atoms, or an arylalkyl group having 7 to 20 carbon atoms,

[0136] R1 to R 11 Two or more adjacent ones of the rings may be connected to each other to form an aliphatic ring having 3 to 20 carbon atoms or an aromatic ring having 6 to 20 carbon atoms, and

[0137] X1 and X2 are each independently hydrogen, halogen, hydroxyl, amino, thiol, silyl, cyano, nitro, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an alkynyl group having 2 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkylaryl group having 7 to 20 carbon atoms, an arylalkyl group having 7 to 20 carbon atoms, a heteroaryl group having 5 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, an aryloxy group having 6 to 20 carbon atoms, an alkylamino group having 1 to 20 carbon atoms, an arylamino group having 6 to 20 carbon atoms, an alkylthio group having 1 to 20 carbon atoms, an arylthio group having 6 to 20 carbon atoms, an alkylsilyl group having 1 to 20 carbon atoms, or an arylsilyl group having 6 to 20 carbon atoms.

[0138] When the polymerization reaction is carried out in the presence of an excess of chain transfer agent (e.g., (Et)2Zn) relative to the catalyst, the olefin polymer chain causes a rapid alkyl transfer between zinc (Zn) and hafnium (Hf), thereby uniformly growing from dialkyl zinc, thereby achieving active polymerization, which is called coordination chain transfer polymerization (CCTP). Commonly used metallocene catalysts cannot be active polymerized by a β-elimination process, and the few catalysts known to be suitable for CCTP only allow a single polymerization of ethylene and α-olefins, making it very difficult to polymerize ethylene and α-olefins by CCTP. Therefore, it is very difficult to use common transition metal compounds as catalysts to perform active polymerization and prepare block copolymers by CCTP.

[0139] On the other hand, the hafnium compound represented by the above Chemical Formula 1 is [N 酰胺基 ,N,C 芳基 ]HfMe2 type complexes exhibit excellent α-olefin introduction ability in the polymerization of ethylene and α-olefin. In particular, the molecular weight of the olefin polymer or the content of α-olefin varies with the content of the chain transfer agent, which shows that the compound can be successfully used in CCTP, and the β-elimination reaction rarely occurs, which is enough to be ignored. That is, the polymerization of ethylene and α-olefin monomers can be carried out by CCTP using the hafnium compound represented by the above chemical formula 1 as living polymerization, and block copolymers with various block compositions can be successfully prepared.

[0140] In addition, CCTP can be converted using hafnium compounds and subjected to anionic styrene polymerization to synthesize polyolefin-polystyrene block copolymers. As described above, hafnium compounds can be used as catalysts for preparing olefin polymers, which is a unique feature that can be achieved by the novel structure of the hafnium compound represented by Chemical Formula 1 above.

[0141] Specifically, in the above chemical formula 1, R1 to R 11 R1 to R2 may each independently be hydrogen, an alkyl group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms. 10 can be hydrogen, and R 11 It may be hydrogen, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms. 10 can be hydrogen, and R 11 It may be hydrogen or an alkyl group having 1 to 20 carbon atoms.

[0142] Alternatively, in the above Chemical Formula 1, R1 to R 11R3 and R4 may be independently hydrogen, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms. In this case, R3 and R4 may be connected to each other to form an aromatic ring having 5 to 20 carbon atoms, such as a benzene ring. Preferably, R3 and R4 may be connected to each other to form a benzene ring, and at the same time, R 11 It may be an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms.

[0143] Alternatively, in the above Chemical Formula 1, R1, R2 and R5 to R 10 can be hydrogen, R3, R4 and R 11 Each may independently be hydrogen or an alkyl group having 1 to 20 carbon atoms, wherein R3 and R4 may be linked to each other to form an aromatic ring having 5 to 20 carbon atoms, such as a benzene ring.

[0144] Meanwhile, X1 and X2 may each independently be hydrogen, an alkyl group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms, and preferably, may each independently be an alkyl group having 1 to 20 carbon atoms, wherein X1 and X2 may be the same as each other.

[0145] In the present invention, the term "alkyl" refers to a straight-chain or branched hydrocarbon moiety.

[0146] In the present invention, the term "alkenyl group" refers to a linear or branched alkenyl group.

[0147] In the present invention, the "aryl group" preferably has 6 to 20 carbon atoms, and specifically may be phenyl, naphthyl, anthracenyl, pyridyl, dimethylanilino, anisole, etc., but is not limited thereto.

[0148] In the present invention, "alkylaryl" refers to an aryl group substituted with the above alkyl group.

[0149] In the present invention, the "arylalkyl group" refers to an alkyl group substituted with the above aryl group.

[0150] In the present specification, the "alkylsilyl group" may be a silyl group substituted with an alkyl group having 1 to 20 carbon atoms, for example, a trimethylsilyl group or a triethylsilyl group.

[0151] In the present invention, "alkylamino" refers to an amino group substituted by the above alkyl groups, such as dimethylamino, diethylamino, etc., but is not limited thereto.

[0152] In the present invention, unless otherwise specified, "hydrocarbon group" means a monovalent hydrocarbon group having 1 to 20 carbon atoms and consisting only of carbon and hydrogen, such as alkyl, aryl, alkenyl, alkynyl, cycloalkyl, alkaryl or aralkyl, regardless of its structure.

[0153] More specifically, the hafnium compound represented by the above Chemical Formula 1 may be a hafnium compound represented by the following Chemical Formula 1a or 1b.

[0154] [Chemical formula 1a]

[0155]

[0156] [Chemical formula 1b]

[0157]

[0158] In the above Chemical Formula 1a and Chemical Formula 1b,

[0159] R 11 is hydrogen, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an alkynyl group having 2 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an arylalkoxy group having 7 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, an alkylaryl group having 7 to 20 carbon atoms, an alkylsilyl group having 1 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms, and

[0160] X1 and X2 are each independently hydrogen, halogen, hydroxyl, amino, thiol, silyl, cyano, nitro, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an alkynyl group having 2 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkylaryl group having 7 to 20 carbon atoms, an arylalkyl group having 7 to 20 carbon atoms, a heteroaryl group having 5 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, an aryloxy group having 6 to 20 carbon atoms, an alkylamino group having 1 to 20 carbon atoms, an arylamino group having 6 to 20 carbon atoms, an alkylthio group having 1 to 20 carbon atoms, an arylthio group having 6 to 20 carbon atoms, an alkylsilyl group having 1 to 20 carbon atoms, or an arylsilyl group having 6 to 20 carbon atoms.

[0161] The hafnium compound may be represented by any one of Chemical Formula 1-1 to Chemical Formula 1-5, but is not limited thereto. Any hafnium compound corresponding to Chemical Formula 1 is included in the present invention.

[0162] [Chemical formula 1-1]

[0163]

[0164] [Chemical formula 1-2]

[0165]

[0166] [Chemical formula 1-3]

[0167]

[0168] [Chemical formula 1-4]

[0169]

[0170] [Chemical formula 1-5]

[0171]

[0172] The hafnium compound of the present invention may be prepared by a step including reacting a compound represented by the following Chemical Formula 2 with a compound represented by the following Chemical Formula 3.

[0173] [Chemical formula 2]

[0174]

[0175] [Chemical formula 3]

[0176] Hf(X1X2)2

[0177] In the above chemical formula,

[0178] R1 to R 11 and X1 and X2 are defined the same as above.

[0179] Meanwhile, when the hafnium compound represented by the above Chemical Formula 1 is prepared, the step of preparing the ligand compound may be variously performed as follows depending on the structure of the finally prepared hafnium compound.

[0180] For example, when R3 and R4 in the ligand compound do not form a ring with each other and R 11 When it is a hydrogen atom, as shown below, the ligand compound can be hydrogenated under a ruthenium catalyst and then reacted with a compound represented by Chemical Formula 3 as a hafnium precursor to prepare a hafnium compound.

[0181] [Reaction formula 1]

[0182]

[0183] Alternatively, when R3 and R4 do not form a ring with each other in the ligand compound structure and R 11 When it is a substituent other than a hydrogen atom, as shown in the following reaction formula 2, an organic lithium compound is first used to introduce R 11 , and then hydrogenated under a ruthenium catalyst to prepare a ligand compound.

[0184] [Reaction 2]

[0185]

[0186] Alternatively, when R3 and R4 are linked to each other to form an aromatic ring having 5 to 20 carbon atoms in the ligand compound structure and R 11 When R is a substituent other than a hydrogen atom, an organolithium compound can be used to introduce R as shown below. 11 , and then, in order to prevent the hydrogenation of aromatic rings such as naphthyl, hydrogenation was carried out over a Pd / C catalyst to prepare a ligand compound.

[0187] [Reaction 3]

[0188]

[0189] That is, the hafnium compound can be prepared by preparing the ligand compound by alkylating and hydrogenating a compound as a precursor of the ligand compound under suitable reagents and reaction conditions, and then introducing hafnium therein to prepare the hafnium compound. Considering the structure of the final compound and experimental conditions, those skilled in the art can appropriately change the specific type of the alkylating agent, the reaction temperature and pressure, etc.

[0190] In the present invention, the organic zinc compound is a material used as a chain transfer agent, which induces chain transfer in a preparation process of a polymerization reaction to prepare a copolymer, and may be specifically a compound represented by the following Chemical Formula 4.

[0191] [Chemical formula 4]

[0192]

[0193] In the above chemical formula 4,

[0194] A is an alkylene group having 1 to 20 carbon atoms, an arylene group having 6 to 20 carbon atoms, or an arylene group having 6 to 20 carbon atoms substituted with halogen, an alkyl group having 1 to 12 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, or an aryl group having 6 to 12 carbon atoms, and

[0195] B is an arylene group having 6 to 12 carbon atoms substituted with an alkenyl group having 2 to 12 carbon atoms.

[0196] Alternatively, A may be an alkylene group having 1 to 12 carbon atoms, an arylene group having 6 to 12 carbon atoms, or an arylene group having 6 to 12 carbon atoms substituted with halogen, an alkyl group having 1 to 12 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, or an aryl group having 6 to 12 carbon atoms, and

[0197] B may be an arylene group having 6 to 12 carbon atoms substituted with an alkenyl group having 2 to 18 carbon atoms.

[0198] Chemical Formula 4 may have a structure in which both ends of the chemical formula are double bonds. For example, when B is an arylene group substituted with an alkenyl group, the arylene group is connected to A and the double bond of the alkenyl group substituted in the arylene group may be located at the outermost portion of Chemical Formula 4.

[0199] When the organozinc compound reacts with one or more olefinic monomers in the presence of the catalyst composition, the olefinic monomers may be inserted between zinc (Zn) of the organozinc compound and the organic group (A) to achieve polymerization.

[0200] The mixed amount of the organic zinc compound may be 1 to 200 equivalents based on 1 equivalent of the transition metal compound of Chemical Formula 1, and specifically, 10 to 100 equivalents based on 1 equivalent of the transition metal compound of Chemical Formula 1.

[0201] The organozinc compound does not contain impurities such as THF and a large amount of magnesium salts and thus can be provided in high purity, and thus can be used as a chain transfer agent and facilitates olefin polymerization.

[0202] The catalyst composition may further include a co-catalyst compound. At this time, the co-catalyst compound is used to activate the transition metal compound represented by Chemical Formula 1, and as a co-catalyst, those known in the art can be used. For example, one or more selected from the following Chemical Formulas 5 to 7 can be used as a co-catalyst.

[0203] [Chemical formula 5]

[0204] -[Al(R a )-O] m -

[0205] [Chemical formula 6]

[0206] D(R a )3

[0207] [Chemical formula 7]

[0208] [LH] + [Z(A)4] - or [L] + [Z(A)4] -

[0209] In the above chemical formula,

[0210] R a are each independently a halogen group, a hydrocarbon group having 1 to 20 carbon atoms, or a hydrocarbon group having 1 to 20 carbon atoms substituted with a halogen,

[0211] m is an integer greater than or equal to 2,

[0212] D is aluminum or boron,

[0213] L is a neutral or cationic Lewis acid,

[0214] Z is a Group 13 element,

[0215] A is each independently an aryl group having 6 to 20 carbon atoms in which one or more hydrogen atoms may be substituted with a substituent, or an alkyl group having 1 to 20 carbon atoms, and

[0216] The substituent of A is a halogen, a hydrocarbon group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or an aryloxy group having 6 to 20 carbon atoms.

[0217] The compound represented by the above Chemical Formula 5 is not particularly limited as long as it is an alkylaluminoxane. Preferred examples thereof include methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, butylaluminoxane, and the like, and a particularly preferred compound is methylaluminoxane.

[0218] The compound represented by the above Chemical Formula 6 is not particularly limited, but preferred examples thereof include trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, dimethylaluminum chloride, triisopropylaluminum, tri-sec-butylaluminum, tricyclopentylaluminum, tripentylaluminum, triisopentylaluminum, trihexylaluminum, trioctylaluminum, ethyldimethylaluminum, methyldiethylaluminum, triphenylaluminum, tri-p-tolylaluminum, dimethylaluminum methoxide, dimethylaluminum ethoxide, trimethylboron, triethylboron, triisobutylboron, tripropylboron, tributylboron, etc. Particularly preferred compounds are selected from trimethylaluminum, triethylaluminum and triisobutylaluminum.

[0219] Examples of the compound represented by the above Chemical Formula 7 include: when Z is boron, for example, dioctadecylmethylammonium tetrakis(pentafluorophenyl)borate [(C 18 H 37 )2N(H)Me] + [B(C6F5)4] -, dioctadecylmethylammonium tetra(phenyl)borate, dioctadecylmethylammonium tetra[3,5-bis(trifluoromethyl)phenyl]borate, tetra(phenyl)borate, triethylammonium tetraphenylborate, tributylammonium tetraphenylborate, trimethylammonium tetraphenylborate, tripropylammonium tetraphenylborate, trimethylammonium tetra(p-tolyl)borate, trimethylammonium tetra(o,p-dimethylphenyl)borate, tributylammonium tetra(p-trifluoromethylphenyl)borate, trimethylammonium tetra(p-trifluoromethylphenyl)borate, tributylammonium tetra(p-trifluoromethylphenyl)borate, tributylammonium tetra(pentafluorophenyl)borate, N, N-Diethylanilinium tetraphenylborate, N,N-diethylanilinium tetraphenylborate, N,N-diethylanilinium tetrakis(pentafluorophenyl)borate, diethylammonium tetrakis(pentafluorophenyl)borate, triphenylphosphonium tetraphenylborate, trimethylphosphonium tetraphenylborate, trimethylammonium tetraphenylborate, tripropylammonium tetraphenylborate, trimethylammonium tetrakis(p-tolyl)borate, tripropylammonium tetrakis(p-tolyl)borate, triethylammonium tetrakis(o-p-dimethylphenyl)borate, trimethylammonium tetrakis(p-trifluoromethylphenyl)borate )tributylammonium borate, trimethylammonium tetrakis(p-trifluoromethylphenyl)borate, tributylammonium tetrakis(pentafluorophenyl)borate, N,N-diethylanilinium tetraphenylborate, N,N-diethylanilinium tetrakis(pentafluorophenyl)borate, diethylammonium tetrakis(pentafluorophenyl)borate, triphenylphosphonium tetraphenylborate, triphenylcarbonium tetrakis(p-trifluoromethylphenyl)borate, triphenylcarbonium tetrakis(pentafluorophenyl)borate, or a combination thereof; when Z is aluminum, for example, triethylammonium tetraphenylaluminum, tributylammonium tetraphenylaluminum, trimethylammonium tetraphenylaluminum, tripropylammonium tetraphenylaluminum , trimethylammonium tetra(p-tolyl)aluminum, tripropylammonium tetra(p-tolyl)aluminum, triethylammonium tetra(o,p-dimethylphenyl)aluminum, tributylammonium tetra(p-trifluoromethylphenyl)aluminum, trimethylammonium tetra(p-trifluoromethylphenyl)aluminum, tributylammonium tetra(pentafluorophenyl)aluminum, N,N-diethylaniline tetraphenylaluminum, N,N-diethylaniline tetra(pentafluorophenyl)aluminum, diethylammonium tetra(pentafluorophenyl)aluminum, triphenylphosphonium tetraphenylaluminum, trimethylphosphonium tetraphenylaluminum, triethylammonium tetraphenylaluminum, tributylammonium tetraphenylaluminum, or a combination thereof, but not limited thereto.

[0220] In particular, the co-catalyst used in the present invention may be a compound represented by the above Chemical Formula 7, and specifically may be dioctadecylmethylammonium tetrakis(pentafluorophenyl)borate.

[0221] In addition, the cocatalyst used in the present invention can be prepared in an anhydrous hydrocarbon solvent. For example, the hydrocarbon solvent can be one or more selected from butane, pentane, neopentane, hexane, cyclohexane, methylcyclohexane, heptane, octane, benzene, toluene, xylene and ethylbenzene, but is not limited thereto. Any hydrocarbon solvent available in the art can be used in an anhydrous form.

[0222] In the present invention, when the co-catalyst is prepared in an anhydrous hydrocarbon solvent,1 In the H NMR spectrum, at least one peak appears in the range of 1.75 ppm to 1.90 ppm and in the range of 1.90 ppm to 2.00 ppm. This indicates that the protons connected to the α-carbon adjacent to the nitrogen, sulfur or phosphorus contained in L show different peaks. For example, when the compound represented by Chemical Formula 1 is [(C 18 H 37 )2N(H)Me] + [B(C6F5)4] - When, in its 1 In the H NMR spectrum, the two protons present in NCH2 can each show a different signal.

[0223] In addition, the hafnium compound represented by Chemical Formula 1 and the co-catalyst may also be used in the form of being supported on a carrier. The carrier may be silica or alumina, but is not limited thereto.

[0224] The olefin monomer introduced as a reaction material in step (S1) may be ethylene, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene and 1-eicosene, or a monomer formed by a mixture thereof, etc. The olefin monomer may be used alone or in combination of two or more.

[0225] Step (S1) can be carried out, for example, in a uniform solution state. At this time, as a solvent, a hydrocarbon solvent or an olefin monomer itself can be used as a medium. The hydrocarbon solvent can be an aliphatic hydrocarbon solvent having 4 to 20 carbon atoms, specifically isobutane, hexane, cyclohexane, methylcyclohexane, etc. The solvent can be used alone or in combination of two or more.

[0226] The polymerization temperature of step (S1) may vary according to the reactants, reaction conditions, etc., but may be specifically 70 to 170° C., specifically 80 to 150° C., or 90 to 120° C. Within the above range, the solubility of the polymer may be increased and the catalyst may be thermally stabilized.

[0227] The polymerization in step (S1) may be carried out in a batch, semi-continuous or continuous manner, or in two or more steps with different reaction conditions.

[0228] The compound prepared in the above step (S1) can be used as a precursor for preparing the polyolefin-polystyrene multi-block copolymer of the present invention by anionic polymerization in the step (S2) described later.

[0229] Step (S2)

[0230] Step (S2) is a step performed subsequent to step (S1) and is a step of forming a polystyrene block by anionic polymerization of a polyolefin block and a styrene monomer in the presence of an alkyllithium compound containing a silicon atom and a triamine compound to prepare a polyolefin-polystyrene multiblock copolymer.

[0231] In step (S2), the styrene monomers can be continuously inserted between the zinc-carbon bonds of the (polyolefin group) 2Zn contained in the compound formed by the above step (S1), and at the same time, the styrene groups present at the ends of the compound formed by step (S1) can participate as copolymerization sites with the styrene monomers and be connected to the polystyrene chain. In addition, the multi-block copolymer prepared by the above method can be easily quenched by the reaction of the end groups with water, oxygen or organic acid, thereby converting the multi-block copolymer into an industrially useful polyolefin-polystyrene multi-block copolymer.

[0232] The styrene-based monomer may be a styrene-based monomer having 6 to 20 carbon atoms. More specifically, the styrene-based monomer may be a styrene-based monomer including ethylene substituted with an aromatic group having 6 to 20 carbon atoms, ethylene substituted with a phenyl group, etc., such as styrene.

[0233] The alkyl lithium compound including a silicon atom may be a compound represented by Chemical Formula 8 below.

[0234] [Chemical formula 8]

[0235] (CH3)3Si(CH2)Li

[0236] Alkyl lithium compounds containing silicon atoms are substances widely used as anionic polymerization initiators, and are easily available for use in the present invention.

[0237] The triamine compound may be a compound represented by Chemical Formula 9 below.

[0238] [Chemical formula 9]

[0239]

[0240] The triamine compound is a compound for improving the reactivity as a base or as a nucleophilic agent of an alkyl lithium compound by well coordinating with lithium, and is easily available and inexpensive.

[0241] The present invention novel uses compounds of chemical formulas 8 and 9 (e.g., Me3SiCH2Li·(PMDETA)) as initiators in step (S2), thereby suppressing the production of polystyrene homopolymers, polyolefin homopolymers, and polyolefin-polystyrene diblock copolymers, and maximizing the production of polyolefin-polystyrene multiblock copolymers, which is the purpose of the present invention.

[0242] The alkyllithium compound containing silicon atoms and represented by Chemical Formula 8 and the triamine compound represented by Chemical Formula 9 may be mixed and introduced into the aliphatic hydrocarbon solvent, or may be introduced sequentially.

[0243] The anionic polymerization temperature of step (S2) may vary depending on the reactants, reaction conditions, etc., but may be specifically 40 to 170°C, more specifically 60 to 150°C, or 90 to 100°C.

[0244] The anionic polymerization in step (S2) can be carried out in batches, semi-continuously or continuously, or in two or more steps with different reaction conditions.

[0245] The anionic polymerization time of step (S2) can vary according to the reaction materials, reaction conditions, etc., but can specifically be 0.5 to 10 hours, 1 to 8 hours, 2 to 7 hours or 4 to 6 hours. When within the above range, it is advantageous to convert the total amount of the introduced styrene monomers into a multi-block copolymer.

[0246] As described above, in the preparation method of the present invention, the polyolefin chain is grown by olefin polymerization using the above-mentioned organic zinc compound represented by the above-mentioned Chemical Formula 4, and then styrene anion polymerization is continuously performed to prepare a polyolefin-polystyrene-based multi-block copolymer, thereby effectively preparing a polyolefin-polystyrene-based multi-block copolymer having improved physical properties compared with the prior art, and thus can be easily used in industry.

[0247] The method for preparing the polyolefin-polystyrene multi-block copolymer according to the example of the present invention is different from the common method for preparing the polyolefin-polystyrene multi-block copolymer (in which styrene and diene are anion polymerized and then subjected to a two-step hydrogenation process), and is characterized in that the polyolefin-polystyrene multi-block copolymer is prepared without a hydrogenation reaction on the double bonds in the main chain of the copolymer. Therefore, the polyolefin-polystyrene multi-block copolymer contained in the thermoplastic resin composition of the present invention is characterized in that the polyolefin-polystyrene multi-block copolymer does not contain unsaturated bonds that are not saturated and exist during the hydrogenation process of the double bonds in the main chain.

[0248] Meanwhile, in order to satisfy the application and the corresponding required physical properties, the thermoplastic resin composition according to the embodiment of the present invention having the above composition may contain appropriate contents of each component. For example, in the present invention, the thermoplastic resin composition may contain (1) polypropylene and (2) polyolefin-polystyrene multi-block copolymer in a weight ratio of 10:90 to 90:10, particularly in a weight ratio of 20:80 to 80:20, and more particularly in a weight ratio of 40:60 to 60:40.

[0249] When the content of the polyolefin-polystyrene multi-block copolymer contained in the thermoplastic resin composition is too small, the impact strength may be reduced, and when the content of the polyolefin-polystyrene multi-block copolymer is too large, the fluidity of the thermoplastic resin may be reduced. The mixing ratio can be controlled in consideration of the importance of the physical properties of the polypropylene and the polyolefin-polystyrene multi-block copolymer.

[0250] The thermoplastic resin composition according to an embodiment of the present invention may optionally further include an inorganic filler along with the polypropylene and the polyolefin-polystyrene-based multi-block copolymer to improve mechanical properties of the thermoplastic resin composition.

[0251] Inorganic filler can be powder filler, sheet filler, fibrous filler or spherical filler, and can use any one thereof or a mixture of two or more thereof. Specifically, powder filler can be natural silicic acid or silicate such as fine powder talc, kaolinite, calcined clay or sericite, carbonates such as precipitated calcium carbonate, heavy calcium carbonate, magnesium carbonate, hydroxides such as aluminum hydroxide or magnesium hydroxide, oxides such as zinc oxide, magnesium oxide or titanium oxide, synthetic silicic acid or silicate such as hydrated calcium silicate, hydrated aluminum silicate, hydrated silicic acid or silicic anhydride and silicon carbide, etc. In addition, sheet filler can be mica, etc. Fibrous filler can be basic magnesium sulfate whisker, calcium titanate whisker, aluminum borate whisker, sepiolite, processed mineral fiber (PMF), potassium titanate, etc. In addition, spherical filler can be glass balls, etc. Wherein, inorganic filler can be talc.

[0252] Furthermore, the inorganic filler may be surface treated to improve the strength properties and molding processability of the thermoplastic resin composition.

[0253] Specifically, the inorganic filler may be physically or chemically surface treated using a surface treatment agent such as a silane coupling agent, a higher fatty acid, a fatty acid metal salt, an unsaturated organic acid, an organic titanate, a resin acid, or polyethylene glycol.

[0254] In addition, the average particle size (D 50 ) may be 1 μm to 20 μm, specifically 3 μm to 15 μm, and more specifically 5 μm to 10 μm. When the average particle size of the inorganic filler is too small, when mixed with polypropylene and polyolefin-polystyrene multi-block copolymer, it is difficult to achieve uniform dispersion due to the aggregation between the inorganic filler particles, and as a result, the effect of improving the mechanical properties of the thermoplastic resin composition may not be significant. In addition, when the average particle size of the inorganic filler is too large, there is a risk of reduced physical properties due to reduced dispersibility of the inorganic filler itself.

[0255] In the present invention, the average particle size (D 50) can be defined as the particle size at 50% of the particle size distribution. In the present invention, the average particle size (D 50 ) can be measured by electron microscopy using, for example, a scanning electron microscope (SEM) or a field emission scanning electron microscope (FE-SEM) or by a laser diffraction method. Specifically, when measuring by the laser diffraction method, the inorganic filler particles can be dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000) to measure the average particle size (D ) at 50% of the particle size distribution in the measuring device. 50 ).

[0256] Based on 100 parts by weight of the thermoplastic resin composition, the content of the above-mentioned inorganic filler can be 0.1 parts by weight to 40 parts by weight. When the content of the inorganic filler in the thermoplastic resin composition is less than 0.1 parts by weight based on 100 parts by weight of the thermoplastic resin composition, the improvement effect due to the inclusion of the inorganic filler is not significant, and when it is greater than 40 parts by weight, the processability of the thermoplastic resin composition may be reduced. More specifically, based on the total weight of the thermoplastic resin composition, the content of the inorganic filler can be 0.1% by weight to 20% by weight.

[0257] The thermoplastic resin composition according to an embodiment of the present invention that meets the above composition and content conditions can be prepared by adding polypropylene and optional inorganic fillers to a polyolefin-polystyrene multi-block copolymer and then heat treating the polypropylene. At this time, the type and content of the polypropylene are the same as above.

[0258] The mixing process can be carried out according to a typical method. Specifically, a super mixer or a ribbon mixer can be used for mixing.

[0259] In addition, according to the needs of the mixing process, additives such as antioxidants, heat stabilizers, UV stabilizers, antistatic agents, etc. may also be included. In order to improve the coating properties, a small amount of adhesive resin or additives with polar groups may be selectively used within an appropriate content range.

[0260] The heat treatment process may be performed at a temperature higher than the melting point of polypropylene and not higher than 210° C. The heat treatment process may be performed using various mixing processing devices such as a twin-screw extruder, a single-screw extruder, a roll mill, a kneader, a Banbury mixer, and the like.

[0261] The thermoplastic resin composition according to one embodiment of the present invention prepared according to the above-mentioned preparation method may have excellent elongation and tensile strength, and exhibit high fluidity.

[0262] Specifically, the thermoplastic resin composition may satisfy the following physical properties (A) to (D).

[0263] (A) Shore A hardness ranges from 1 to 90,

[0264] (B) Permanent compression set is 0 to 80%,

[0265] (C) melt flow rate (MFR, 230°C, 2.16 kg) of 0.1 to 300 g / 10 min,

[0266] (D) Melt flow rate (MFR, 230°C, 5 kg) is 0.1 to 500 g / 10 min.

[0267] (A) The Shore A hardness may be 1 to 90, specifically 10 to 90, and more specifically 20 to 90.

[0268] Shore A hardness can be measured according to ASTM D2240 standard.

[0269] (B) The permanent compression set may be 0 to 80%, specifically 1 to 80%, and more specifically 10 to 70%.

[0270] Permanent compression set can be measured according to ASTM D-3574.

[0271] (C) The melt flow rate (MFR, 230° C., 2.16 kg) may be 0.1 to 300 g / 10 min, specifically 0.2 to 200 g / 10 min, and more specifically 0.5 to 100 g / 10 min.

[0272] (D) The melt flow rate (MFR, 230° C., 5 kg) may be 0.1 to 500 g / 10 min, specifically 0.5 to 300 g / 10 min, and more specifically 2 to 150 g / 10 min.

[0273] According to ASTM-D 1238, the melt flow rate was measured under the conditions of 230° C. and 2.16 kg load and 230° C. and 5 kg load, respectively.

[0274] The thermoplastic resin composition according to an embodiment of the present invention can be used for hollow molding, extrusion molding or injection molding in various fields and applications such as packaging, construction, household goods, etc., such as automobiles, wires, toys, textiles or medical products. In particular, the thermoplastic resin composition has excellent toughness and impact strength at both low temperatures and room temperatures, and also has excellent physical properties such as heat resistance and rigidity, and can therefore be used for interior and exterior parts of automobiles.

[0275] According to another embodiment of the present invention, there are provided a molded body and an automobile part manufactured by using the thermoplastic resin composition satisfying the above physical property requirements.

[0276] The molded body may specifically be a blow molded body, an inflation molded body, a cast molded body, an extrusion laminated body, an extrusion molded body, a foamed body, an injection molded body, a sheet, a film, a fiber, a monofilament, a nonwoven fabric, or the like.

[0277] In addition, the automobile parts may be interior and exterior parts of an automobile, and the like.

[0278] Example

[0279] Hereinafter, the present invention will be described in detail with reference to Examples. However, the following Examples are merely illustrative of the present invention and are not intended to limit the scope of the present invention.

[0280] <Preparation of transition metal compound>

[0281] Preparation Example 1

[0282] (i) Preparation of ligand compounds

[0283] Isopropyl lithium (0.45 mL, 0.36 mmol, 0.79 M pentane solution) was slowly added to 2-naphthyl-1,10-phenanthroline (0.789 g, 2.58 mmol) in toluene (8 mL) at -10 ° C. After stirring at room temperature for 3 hours, degassed H2O (3 mL) was added. The water layer was removed by a syringe under N2. The solvent was removed using a vacuum line, and the residue was dissolved in degassed ethanol (15 mL) and THF (5 mL). The solution was transferred to a bomb reactor containing Pd / C (0.242 mmol, 10 mol%) under N2. After H2 gas was charged to 5 bar, the mixture was stirred at room temperature for 12 hours. H2 gas was released and the catalyst residue was filtered on diatomaceous earth and removed. The solvent was removed and the residue was purified by silica gel column chromatography using ethyl acetate / hexane (1 / 3, v / v). A light yellow viscous solid (0.085 g, 73%) was obtained. 1 H NMR and 13 C NMR spectrum is shown in Figure 1 middle.

[0284] - 1H NMR (C6D6): δ8.58(d,J=7.8Hz,H),7.75(d,J=9.0Hz,H),7.70(d,J=9.6Hz,H),7.66(d, J=7.2Hz,H),7.63(d,J=6.6Hz,H),7.32(m,4H),7.18(d,J=8.4Hz,H),6.99(d,J=7.8Hz ,H),6.39(s,H,NH),2.93(m,H),2.79(m,H),2.70(dt,J=4.8Hz,H),1.70(m,H),1.63(m ,H),1.47(m,H),0.81(d,J=7.2Hz,3H,CH(CH3)2),0.76(d,J=7.2Hz,3H,CH(CH3)2)ppm.

[0285] - 13 C{ 1 H}NMR(C6D6): δ18.34,18.77,24.43,26.78,32.52,56.73,112.78,116.67,122.62,125.59,126.10,126.51,1 26.61,126.86,128.14,128.69,129.03,129.28,132.20,134.71,136.41,137.64,139.79,141.75,155.92ppm.

[0286] - m / z calculated value ([M + ]C 25 H 24 N2) 352.4800. Measured value: 352.1942.

[0287] (ii) Preparation of transition metal compounds

[0288] [Chemical formula 1-3]

[0289]

[0290] At -78 ° C, MeMgBr (1.24 mL, 3.11 M ether solution) was added dropwise to a stirred HfCl4 suspension (0.300 g, 0.938 mmol) in toluene (8 mL). After stirring at a temperature of -40 ° C to -35 ° C for 1 hour, it was cooled to -78 ° C again. A solution (0.24 g, 0.94 mmol) of a ligand compound (0.366 g, 1.00 mmol) in toluene (4 mL) was added dropwise. The resulting solution was stirred at a controlled temperature of -40 ° C to -35 ° C for 2 hours, and then stirred at room temperature overnight. A vacuum line was used to remove the solvent, and the residue was extracted with toluene (50 mL). A dark brown powder (0.226 g, 47%) was obtained by pulverizing in hexane. 1 H NMR and 13 C NMR spectrum is shown in Figure 2 middle.

[0291] - 1 H NMR (C6D6): δ8.66(d,J=7.8Hz,H), 8.50(d,J=7.8Hz,H), 7.92(d,J=9.0Hz,H), 7.83(d,J=7.2Hz, H),7.76(d,J=8.4Hz,H),7.62(d,J=7.8Hz,H),7.40(td,J=7.2Hz,H),7.32(m,H),7.14(d,J=7.8H z,H),6.77(d,J=7.2Hz,H),4.02(m,H),2.80(m,H),2.62(dt,J=6.0Hz,H),2.55(m,H),1.88(m,H) ,1.72(m,H), 1.09 and 1.04(d,J=6.6Hz,6H,CH(CH3)2), 0.82(s,3H,HfCH3), 0.81(s,3H,HfCH3)ppm.

[0292] - 13 C{ 1 H}NMR(C6D6): δ18.55,21.28,23.07,25.44,32.58,60.98,63.06,66.88,112.37,119.64,120.21,124.55,125.48,12 6.81,126.97,129.31,129.97,130.26,131.25,133.82,135.51,140.97,141.44,143.94,150.14,164.58,209.13ppm.

[0293] - Analytical calculation value (C 27 H 28HfN2): C, 58.01; H, 5.05; N, 5.01%.

[0294] - Found: C, 57.91; H, 5.01; N, 5.11%.

[0295] <Preparation of co-catalyst>

[0296] In a glove box, excess K + [B(C6F5)4] - (0.633 g, 0.881 mmol, assumed pure) and (C 18 H 37 )2N(H)Me] + [Cl] - The solution of (0.404 g, 0.705 mmol) was reacted for 1 hour. After filtering on diatomaceous earth, the solvent was removed using a vacuum line. The residue was dissolved in methylcyclohexane (4 mL) and then filtered on diatomaceous earth again. The solvent was removed to produce a yellow oily compound, which was used without further purification (0.797 g, 93%).

[0297] - 1 H NMR (C6D6): δ3.15(br,H,NH),1.97(m,2H,NCH2),1.80(m,H,NCH2),1.51(d,J=6.0Hz,3H,NCH3),1.45-1.29(m,48H),1.26( quintet,J=7.2Hz,4H),1.13(quintet,J=7.2Hz,4H),0.94(t,J=7.8Hz,6H),0.88(quintet,J=7.8Hz,4H),0.81(m,4H)ppm.

[0298] - 19 F NMR(C6D6): δ-132.09,-161.75,-165.98.

[0299] <Preparation of Organozinc Compounds>

[0300]

[0301] Borane dimethyl sulfide (1.6mL, 3.2mmol) was slowly introduced into triethylborane (0.6g) under stirring, and then reacted for 90 minutes. The mixture was slowly introduced into divinylbenzene (3.8g) dissolved in anhydrous ether (10mL) cooled to -20°C, and then stirred overnight. The solvent was removed with a vacuum pump, and then diethylzinc (0.8g) was added. The reaction was carried out at 0°C for 5 hours, and the triethylborane produced was removed by vacuum distillation. At 40°C, excess divinylbenzene and diethylzinc were removed by vacuum distillation. Methylcyclohexane (150mL) was added again to dissolve the product, and then the solid compound generated as a by-product was filtered and removed using diatomaceous earth to prepare the organic zinc compound represented by the above chemical formula.

[0302] <Preparation of polyolefin-polystyrene multi-block copolymer>

[0303] Preparation Example 1

[0304] A Parr reactor (1 gallon) was dried under vacuum at 120°C for 2 hours. A solution of Oc3Al (trioctylaluminum, 1466.4 mg, 1,000 μmol-Al) in methylcyclohexane (1,200 g) was added to the reactor. The mixture was stirred at 120°C for 1 hour using a heating jacket, and then the solution was removed using a cannula.

[0305] The reactor was filled with methylcyclohexane (600 g) containing Oc3Al (715.6 mg, 488 μmol-Al / 25 wt% hexane solution) as a scavenger and 1-hexene (560 g) as an olefin monomer, and the temperature was set to 90° C. A solution of an organozinc compound (3,720 μmol) in methylcyclohexane (3.85 g) was filled as a chain transfer agent, and then a solution containing [(C 18 H 37 )2N(H)Me] + [B(C6F5)4] - A methylcyclohexane solution (1.68 g) of the activated transition metal compound (12.0 μmol-Hf) of Preparation Example 1 was added. The polymerization was carried out for 40 minutes while the pressure in the reactor was maintained at 25 bar by opening the valve of the ethylene tank. The temperature was adjusted in the range of 90 to 120° C., and the remaining ethylene gas was discharged.

[0306] When the temperature reached 90°C, Me3SiCH2Li·(PMDETA) solution prepared by mixing Me3SiCH2Li (244.8 mg, 2.6 mmol) and PMDETA (495.1 mg, 2.86 mmol) in methylcyclohexane (3.85 g) was added. The temperature was maintained at 90°C for 30 minutes during stirring, and then styrene (109 g) was injected. The temperature was adjusted in the range of 90 to 100°C using a heating jacket.

[0307] According to the aliquot 1 H NMR analysis confirmed that styrene was completely converted. After styrene was completely converted, 2-ethylhexanoic acid and ethanol were continuously injected. The resulting polymer block (300 g) was dried in a vacuum oven at 80° C. overnight.

[0308] Preparation Example 2

[0309] A polyolefin-polystyrene-based multi-block copolymer was prepared in the same manner as in Preparation Example 1, except that the amount of the organic zinc compound and the amount of styrene used were different, as shown in Table 1 below.

[0310] Comparative Preparation Example 1

[0311] As commercially available SEBS, G1651 from Kraton Company was used.

[0312] Comparative Preparation Example 2

[0313] A polyolefin-polystyrene-based multi-block copolymer was prepared by the following method using a compound represented by the following chemical formula as a transition metal compound.

[0314] [Comparative Chemical Formula 1]

[0315]

[0316] A solution of trimethylaluminum (14.4 mg, 200 umol-Al) dissolved in methylcyclohexane (17 g) was injected into the high pressure reactor. The catalyst poisons in the high pressure reactor were purged at 100°C for 1 hour, and the solution was removed using a cannula.

[0317] The organozinc compound (49.1 mg, 150 μmol) was dissolved in methylcyclohexane (40 g) and introduced into the high pressure reactor, and the temperature was raised to 80° C. The transition metal compound and (C 18 H 37 )N(Me)H + [B(C6F5)4] -The solution obtained by stirring 2 hours in benzene with 4.0 μmol of ethyl acetate (4.0 μmol) was diluted with a solution (1.0 g) obtained by dissolving trioctyl aluminum (50 μmol, 18.3 mg) in methylcyclohexane (15 g). Immediately after the catalyst solution was injected into the high-pressure reactor, an ethylene-propylene mixed gas was injected therein at a pressure of 20 bar (propylene 10 bar). The temperature was adjusted within the range of 95 to 115° C. Due to the consumption of the monomer, the pressure was gradually reduced, and the polymerization process was carried out at 45° C. for 60 minutes, and then the remaining gas was discharged.

[0318] Me3SiCH2Li (150 μmol, 14.1 mg) and PMDETA (150 μmol, 26 mg) were mixed with methylcyclohexane (1.0 g) and then injected into the reactor and stirred for another 30 minutes. The stirring temperature was maintained at 90°C to 100°C. Styrene (7.8 g) was injected into the high-pressure reactor and then reacted for 5 hours while maintaining the temperature at 90°C to 100°C to completely convert the styrene monomer. After the styrene monomer was completely converted, acetic acid and ethanol were continuously injected. The polymer was obtained and then dried overnight in a vacuum oven at 180°C.

[0319] Table 1

[0320]

[0321] Experimental Example 1

[0322] For the polyolefin-polystyrene-based multi-block copolymers of Implementation Examples 1 and 2 and Comparative Preparation Examples 1 and 2, physical properties of each copolymer were measured according to the following conditions and methods, and the results are shown in Table 2 below.

[0323] (1) Storage modulus (E'), loss modulus (E") and tanδ value

[0324] The measurement was performed using a dynamic mechanical analysis (DMA) apparatus by increasing the temperature from -90°C to 100°C at a rate of 5°C per minute at a frequency of 1 Hz and a strain of 0.1%.

[0325] (2) tanδ peak height

[0326] The y value when the tan δ value is maximum is measured in a graph showing the change in loss tangent (tan δ) (y axis) with temperature (x axis) in the temperature range of -80°C to 40°C.

[0327] (3) tanδ peak half width

[0328] The temperatures having the half value of the tan δ peak height are set as T1 and T2, respectively, to calculate the width (T2-T1) between T1 and T2.

[0329] Table 2

[0330]

[0331] Experimental Example 2

[0332] (1) Weight average molecular weight (Mw, g / mol) and polydispersity index (PDI)

[0333] The weight average molecular weight (Mw, g / mol) and number average molecular weight (Mn, g / mol) were determined by gel permeation chromatography (GPC), and the polydispersity index (PDI) was calculated by dividing the weight average molecular weight by the number average molecular weight.

[0334] - Column: PL Olexis

[0335] -Solvent: TCB (trichlorobenzene)

[0336] -Flow rate: 1.0ml / min

[0337] -Sample concentration: 1.0mg / ml

[0338] -Injection volume: 200μl

[0339] - Column temperature: 160℃

[0340] -Detector: Agilent high temperature RI detector

[0341] -Standard: Polystyrene

[0342] - Using the Mark-Houwink equation (K = 40.8 × 10 -5 , α=0.7057) Molecular weight was calculated by universal calibration (2) Impact strength

[0343] Using a twin-screw extruder, 90 wt% of a polypropylene homopolymer and 10 wt% of the copolymer of the above-mentioned Example Preparation or Comparative Preparation Example were mixed and the mixture was prepared as a sample.

[0344] Impact strength (notched Izod, J / m) was measured at temperatures of -30°C and 25°C, respectively, according to standard measurement ASTM D256.

[0345] Table 3

[0346]

[0347] Example 1 - Preparation of Thermoplastic Resin Composition

[0348] To 50 parts by weight of the polyolefin-polystyrene multi-block copolymer prepared in the above-mentioned Example 1, 50 parts by weight of a high crystalline impact copolymer polypropylene (CB5230, a product of Korea Petrochemical Industry Co., Ltd.) having a melt index (230° C., 2.16 kg) of 30 g / 10 min was added, and solution blending was performed in xylene using a reactor to prepare a thermoplastic resin composition compound. At this time, the temperature was 200° C. to 230° C., the impeller speed was 400 rpm, and the blending time was 4 hours. After the blending was completed, the compound was recovered and then dried overnight in a vacuum oven at 100° C.

[0349] Example 2 - Preparation of Thermoplastic Resin Composition

[0350] A thermoplastic resin composition compound was prepared in the same manner as in Example 1, except that the content of the polyolefin-polystyrene multi-block copolymer prepared in Preparation Example 1 and the content of the high crystalline impact copolymer polypropylene were changed to 80 parts by weight and 20 parts by weight, respectively.

[0351] Example 3 - Preparation of Thermoplastic Resin Composition

[0352] A thermoplastic resin composition compound was prepared in the same manner as in Example 1, except that the polyolefin-polystyrene-based multi-block copolymer prepared in Example 2 was used instead of the polyolefin-polystyrene-based multi-block copolymer prepared in Example 1.

[0353] Example 4 - Preparation of Thermoplastic Resin Composition

[0354] A thermoplastic resin composition compound was prepared in the same manner as in Example 2, except that the polyolefin-polystyrene-based multi-block copolymer prepared in Example 2 was used instead of the polyolefin-polystyrene-based multi-block copolymer prepared in Example 1.

[0355] Comparative Example 1 - Preparation of a Thermoplastic Resin Composition

[0356] A thermoplastic resin composition compound was prepared in the same manner as in Example 1, except that the polyolefin-polystyrene-based multi-block copolymer prepared in Comparative Preparation Example 1 was used instead of the polyolefin-polystyrene-based multi-block copolymer prepared in Example Preparation Example 1.

[0357] Comparative Example 2 - Preparation of Thermoplastic Resin Composition

[0358] A thermoplastic resin composition compound was prepared in the same manner as in Example 2, except that the polyolefin-polystyrene-based multi-block copolymer prepared in Comparative Preparation Example 1 was used instead of the polyolefin-polystyrene-based multi-block copolymer prepared in Example Preparation Example 1.

[0359] Comparative Example 3 - Preparation of Thermoplastic Resin Composition

[0360] A thermoplastic resin composition compound was prepared in the same manner as in Example 1, except that the polyolefin-polystyrene-based multi-block copolymer prepared in Comparative Preparation Example 2 was used instead of the polyolefin-polystyrene-based multi-block copolymer prepared in Comparative Preparation Example 1.

[0361] Comparative Example 4 - Preparation of Thermoplastic Resin Composition

[0362] A thermoplastic resin composition compound was prepared in the same manner as in Example 2, except that the polyolefin-polystyrene-based multi-block copolymer prepared in Comparative Preparation Example 2 was used instead of the polyolefin-polystyrene-based multi-block copolymer prepared in Comparative Preparation Example 1.

[0363] Experimental Example 3

[0364] For the thermoplastic resin compositions of Examples 1 to 4 and Comparative Examples 1 to 4, physical properties were measured according to the following conditions and methods, and the results are shown in Table 4 below.

[0365] (1) Measurement of ethylene, α-olefin and styrene content

[0366] The copolymers of Preparation Example 1 and Comparative Preparation Example 1 were measured by NMR. Using a Bruker 600 MHz AVANCE III HD NMR device, the measurement was performed under the conditions of ns=16, d1=3s, solvent=TCE-d2, and 373 K. 1 H NMR, and then calibrate the TCE-d2 solvent peak to 6.0ppm. The CH3 of 1-propylene was confirmed at 1ppm, and the CH3 related peak (triplet) of butyl branched chain was confirmed by 1-hexene near 0.96ppm to calculate the content. In addition, the aromatic peak near 6.5 to 7.5ppm was used to calculate the content of styrene.

[0367] (2) Measurement of hardness (Shore A)

[0368] The hardness was measured using GC610 STAND for Durometer from TECLOCK Corporation and Shore Durometer Type A from Mitutoyo Corporation according to ASTM D2240 standard.

[0369] (3) Permanent compression set

[0370] For the specimens prepared in the form of cylinders having a thickness of 12.5 ± 0.5 mm and a diameter of 29 ± 0.5 mm using the thermoplastic resin compositions of each of Examples 1 to 4 and Comparative Examples 1 to 4, the measurements were performed according to ASTM D-395. The specimens were placed between two parallel metal plates, and a spacer having a thickness of 9.5 ± 0.02 mm was inserted therein. After compression at room temperature (20 ± 0.5 ° C), the specimens were taken out of the compression device after 22 hours, left to stand at room temperature (20 ± 0.5 ° C) for 30 minutes, and then their thickness was measured. Three specimens were used in the same experimental example, and the permanent compression set was calculated by the following calculation formula 1.

[0371] [Calculation formula 1]

[0372] Permanent compression set (%) = [(t0-t f ) / (t0-t s )]×100

[0373] t0 is the initial thickness of the sample, t f is the thickness of the sample when cooled after heat treatment, t s is the thickness of the spacer.

[0374] (4) Melt flow rate (MFR)

[0375] According to ASTM-D 1238, the melt flow rate was measured under the conditions of 230° C. and 2.16 kg load and 230° C. and 5 kg load, respectively.

[0376] Table 4

[0377]

[0378] As can be seen in Table 4 above, when Examples 1 and 3 are compared with Comparative Examples 1 and 3, and Examples 2 and 4 are compared with Comparative Examples 2 and 4 (all having the same multi-block copolymer content), respectively, it is confirmed that the thermoplastic resin compositions of Examples 1 to 4 each comprising the polyolefin-polystyrene-based multi-block copolymer of Comparative Preparation Example 1 or 2 have significantly higher MFR values ​​and lower permanent compression set values, and thus exhibit excellent flowability as well as excellent restoring force, compared with the thermoplastic resin compositions of Comparative Examples 1 to 4 each comprising the polyolefin-polystyrene-based multi-block copolymer of Comparative Preparation Example 1 or 2.

[0379] In addition, although the thermoplastic resin compositions of Examples 1 to 4 exhibited slightly lower hardness than the thermoplastic resin compositions of Comparative Examples 1 to 4, it was confirmed that the hardness values ​​were still high. Thus, it was confirmed that the thermoplastic resin compositions of Examples 1 to 4 exhibited high fluidity and high resilience while maintaining high hardness.

Claims

1. A thermoplastic resin composition comprising: (1) Polypropylene; and (2) A polyolefin-polystyrene-based multi-block copolymer which satisfies the following conditions (a) and (b) in a graph showing the change in loss tangent tan δ as the y-axis with temperature as the x-axis obtained by dynamic mechanical analysis (DMA): (a) The height of the tan δ peak is 0.45 to 0.60; (b) The half width of the tanδ peak is from 22.5°C to 30.0°C, in, The polyolefin-polystyrene multi-block copolymer is one or more selected from the group consisting of polystyrene-poly(ethylene-co-propylene)-polystyrene block copolymer, polystyrene-poly(ethylene-co-1-butene)-polystyrene block copolymer, polystyrene-poly(ethylene-co-1-pentene)-polystyrene block copolymer, polystyrene-poly(ethylene-co-1-hexene)-polystyrene block copolymer, polystyrene-poly(ethylene-co-1-heptene)-polystyrene block copolymer and polystyrene-poly(ethylene-co-1-octene)-polystyrene block copolymer, The weight ratio of the (1) polypropylene to the (2) polyolefin-polystyrene multi-block copolymer is 10:90 to 90:

10. The tanδ peak height represents the y value at which the tanδ value obtained by dynamic thermomechanical analysis is the maximum in the range of -80°C to 40°C on the x-axis. Here, when the temperatures each having the half value of the tan δ peak height defined as the tan δ value in condition (a) are low temperature T1 and high temperature T2, respectively, the tan δ peak half width refers to T2-T1, which is the temperature range between T1 and T2.

2. The thermoplastic resin composition according to claim 1, wherein Under the condition (a), the tan δ peak appears as a peak in the range of -50°C to -30°C.

3. The thermoplastic resin composition according to claim 1, wherein Under the condition (b), the half width of the tan δ peak is 23.0°C to 29.0°C.

4. The thermoplastic resin composition according to claim 1, wherein The polyolefin-polystyrene multi-block copolymer also satisfies the following conditions (c) and (d): (c) a tan delta value of 0.10 to 0.30 at -10°C to -30°C; (d) The tan δ value at 15°C to 30°C is 0.05 to 0.

50.

5. The thermoplastic resin composition according to claim 4, wherein The polyolefin-polystyrene multi-block copolymer has a storage modulus value E' of 1 to 200 MPa and a loss modulus value E" of 1 to 100 MPa at -10°C to -30°C.

6. The thermoplastic resin composition according to claim 4, wherein The polyolefin-polystyrene multi-block copolymer has a storage modulus value E' of 0.1 to 50 MPa and a loss modulus value E" of 0.01 to 5 MPa at 15° C. to 30° C.

7. The thermoplastic resin composition according to claim 1, wherein The weight average molecular weight of the polyolefin-polystyrene multi-block copolymer is 40,000 g / mol to 300,000 g / mol.

8. The thermoplastic resin composition according to claim 1, wherein The molecular weight distribution of the polyolefin-polystyrene multi-block copolymer is 1.0 to 3.

0.

9. The thermoplastic resin composition according to claim 1, wherein The polyolefin-polystyrene multi-block copolymer comprises 10 wt % to 30 wt % of polystyrene blocks.

10. The thermoplastic resin composition according to claim 1, wherein The polyolefin-polystyrene multi-block copolymer is prepared without hydrogenating double bonds in the main chain of the copolymer.

11. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition is a thermoplastic resin composition that satisfies the following physical properties (A) to (D): (A) Shore A hardness ranges from 1 to 90, (B) Permanent compression set of 0 to 80%, (C) a melt flow rate of 0.1 g / 10 min to 300 g / 10 min measured at 230°C and a load of 2.16 kg, (D) A melt flow rate measured at 230° C. and a load of 5 kg is 0.1 g / 10 min to 500 g / 10 min.

Citation Information

Patent Citations

  • Organozinc compound including polyolefin-polystyrene block copolymers and method for manufacturing thereof

    KR101657925B1

  • anti-alpha synuclein antibodies

    KR1020200099168A

  • Foldable Touch Sensor Panel, Laminated Member and Display Device therewith

    KR1020210103396A

  • Hydrogenated copolymer, composition, and molded article

    CN108473638A

  • Polypropylene resin composition with excellent paintability

    KR1020120116685A